Pelatihan Foto Produk dan Pemasaran Online untuk Mengembangkan UMKM di Desa Semen - Fitriyah, Faridatul; Rochmah, Naila Nur; Hakim, Lukman; Kurniawati, Erlina; Rusfadi, Tasya Sintiya; Arifan, Mahdha Viki; Azizah, Putri Nur; Rosyidah, Afifah Dzakiyatur; Firynasari, Firynasari; Avanti, Laila Syafina; Nada, Erika Qothrun; Rosy, Mochammad Ilham Fahrur; Ilahi, Wifqi Ni’matul; Ariyanto, Ikhroj Biarfiunsta Rizki; Hidayah, Anisatul; Mulyani, Hari Dwi (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2024)
The aim of this service is to improve the economic level of the Cement Village community through product photo training and online marketing. The method used is participatory action research (PAR), which actively involves the community in every stage of its implementation. Based on the data collected, the development of MSMEs in Cement Village has not been stable due to the lack of adequate forums and support for MSME actors. Therefore, the training provided covers various important aspects, such as creating logos, product photos, business identity numbers (NIB), halal certification, and online marketing. The results of the questionnaire show that online marketing and product photos are the topics most interesting to MSMEs. After attending training, MSME players succeeded in having a logo and product photo, which is the first step before proceeding to online marketing. The media used in online marketing training are popular platforms such as Facebook, Instagram, and WA Business. With this program, it is hoped that the people of Cement Village can be more advanced in marketing their products effectively so that they can improve the local economy significantly.